Beyond the Binary: Gender and Legal Personhood in Islamic Law: Book Review - Zulfa Asifa Albania; Ika Nur Pujiastuti (Journal of Islamic Studies and Education, 2025)
"Beyond The Binary: Gender and Legal Personhood in Islamic Law" by Saadia Yacoob is a groundbreaking work that challenges the traditional binary understanding of gender in Islamic law and explores the legal personhood of individuals who fall outside this binary. The book argues that Islamic law, when interpreted through a lens of justice and equity, can accommodate diverse gender identities and experiences. Yacoob meticulously examines the historical and contemporary interpretations of gender in Islamic law, highlighting the limitations of the binary framework and its impact on the lives of individuals who do not conform to traditional gender norms. She then presents a compelling case for a more inclusive and nuanced understanding of gender and legal personhood within Islamic law, drawing on Islamic legal principles, feminist scholarship, and contemporary legal developments.